Negatyvumas kaip konstituojamasis faktorius šiuolaikinės psichoanalizės ir postmodernizmo kontekste - Ignatovich, Ekaterina (Problemos, 2004)
The article in question is concerned with the possibilities of overlapping of the conceptual fields of the contemporary psychoanalysis and postmarxism. The common foundation of the both theoretical discourses is the anti-essentialist attitude. E. Laclau, as one of the most prominent postmarxiit thinkers, proposes the thesis of “Impossibility of Society”, which implies that society as a discursive formation is based upon its immanent antagonism, inherent limit, which constitutes ideological statements about the fullness and completeness of the social. Very similarly sound the assertions of S. Žižek, the most acknowledged follower of J. Lacan, namely, that both on the subject's level and on the society's one we have to do with symbolic compensations, which are condensed around certain impossible traumatic experience – “the kernels of the Real”. The article examines these ways of rethinking and reformulating of such established notions as “unconscious”, “symptom”, “ideology”, “hegemony” and so on, actually the way of providing a quite different theoretical language, which respond adequately to the dislocating effects of the contemporary post-industrial society.
Keywords: psychoanalysis; post-Marxism; anti-essentialist attitude; negativity; social antagonism